An observational study towards demographic profiling to assess the health seeking behaviour of transgenders in Chittoor town, Andhra Pradesh - Vinayagam, Akshika; Natarajan, Bharath; Koni, Kiranmayi; Tarugu, Jayanthi; Ramapuram, Prashanthi; Elumalai, Meenakshi Arumugam (International Journal Of Community Medicine And Public Health, 2025)
Transgenders (TGs) individuals, whose gender identity does not align with the sex assigned at birth, form less than 1% of the global population, with about 4.87 lakh in India and approximately 50,000 in Andhra Pradesh as of 2022. Existing research focuses primarily on sexual practices and HIV/STDs, leaving gaps in understanding their health problems and healthcare-seeking behaviour. Hence, this study was conducted to assess the healthcare-seeking behaviour of TG individuals. A descriptive research design with non-probability snowball sampling was adopted and data was collected through interviews with 15 TGs in Chittoor town, Andhra Pradesh, India. A self-structured questionnaire assessed their health-seeking behaviour. Data were analyzed using descriptive and inferential statistics. Among 15 TG participants, majority were residing in urban area (15, 100%), engaged in begging (14, 93%), unmarried (15, 100%) and sought health services from private hospitals (13, 87%). Most participants (11, 73%) had moderate health-seeking behaviour, while 2 (13.5%) had high and 2 (13.5%) had poor health-seeking behaviour, due to common barriers including refusal of medical care (13, 87%) and lack of health insurance (13, 87%). Chi-square test showed a statistically significant association between health-seeking behaviour and both occupation and family support during illness (p≤0.05). The study provides key insights into the health-seeking behaviour of TGs in Chittoor town. Despite moderate healthcare engagement, issues like lack of insurance, delayed care, and discrimination persist. Inclusive policies and targeted interventions are needed to improve access and quality of care.